A Water‐Stable Dual‐Channel Luminescence Sensor for UO22+ Ions Based on an Anionic Terbium(III) Metal–Organic Framework. Issue 32 (15th May 2017) - Ye, Junwei; Bogale, Raji F.; Shi, Yangwei; Chen, Yanzhen; Liu, Xigang; Zhang, Siqi; Yang, Yaoyao; Zhao, Jianzhang; Ning, Guiling
Abstract: A stable 3D Tb III ‐based metal–organic framework [Tb(BPDC)2 ]⋅(CH3 )2 NH2 (DUT‐101) was synthesized, and it is the first efficient dual‐channel luminescence sensor for aqueous UO2 2+ ions. DUT‐101 contains an anionic three‐dimensional framework and protonated dimethylamine molecules embedded within the channels. The intense green emission of DUT‐101 could be highly selectively and sensitively quenched by UO2 2+ ions even in the presence of other competing metal ions. A possible sensing mechanism was proposed based on both suppression of luminescence resonance energy transfer and enhancement of intermolecular electron transfer. Furthermore, visual green fluorescent test papers based on DUT‐101 were fabricated and could be used to discriminate UO2 2+ ions among various metal ions. Abstract : Watching out for uranium : A water‐stable 3D Tb III ‐based metal–organic framework is synthesized, and it is the first efficient dual‐channel response luminescence sensor for aqueous UO2 2+ ions. The intense green emission of DUT‐101 can be highly selectively and sensitively quenched by UO2 2+ ions even in the presence of other competing metal ions.